2020
DOI: 10.1021/acsomega.0c04525
|View full text |Cite
|
Sign up to set email alerts
|

TemporalIn VitroRaman Spectroscopy for Monitoring Replication Kinetics of Epstein–Barr Virus Infection in Glial Cells

Abstract: Raman spectroscopy can be used as a tool to study virus entry and pathogen-driven manipulation of the host efficiently. To date, Epstein–Barr virus (EBV) entry and altered biochemistry of the glial cell upon infection are elusive. In this study, we detected biomolecular changes in human glial cells, namely, HMC-3 (microglia) and U-87 MG (astrocytes), at two variable cellular locations (nucleus and periphery) by Raman spectroscopy post-EBV infection at different time points. Two possible phenomena, one attribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 138 publications
4
45
0
Order By: Relevance
“…The peak position completely matches with the JCPDS no 20-0781 and reveals the existence of NiCo 2 O 4 phase in the inverse spinal crystal structure [37]. Further, to understand the vibrational mode and validation of XRD results, Raman spectroscopy has been performed on the film using 633 nm excitation wavelength due to its versatile nature [38][39][40][41][42][43][44] The morphology of white translucent film of NiCo 2 O 4 , as revealed by XRD and Raman measurements, have been studied using SEM ( Figure 2) revealing a film consisting of nanoneedles. Figure 2a is showing the top view image of the film revealing vertically aligned nanoneedle architecture with sharp tips.…”
Section: Resultsmentioning
confidence: 71%
“…The peak position completely matches with the JCPDS no 20-0781 and reveals the existence of NiCo 2 O 4 phase in the inverse spinal crystal structure [37]. Further, to understand the vibrational mode and validation of XRD results, Raman spectroscopy has been performed on the film using 633 nm excitation wavelength due to its versatile nature [38][39][40][41][42][43][44] The morphology of white translucent film of NiCo 2 O 4 , as revealed by XRD and Raman measurements, have been studied using SEM ( Figure 2) revealing a film consisting of nanoneedles. Figure 2a is showing the top view image of the film revealing vertically aligned nanoneedle architecture with sharp tips.…”
Section: Resultsmentioning
confidence: 71%
“…It has been reported that I10 and EBV take 4 to 6 h to infect the epithelial cells ( 19 , 20 ). Prior to the incubation of I10 with AGS cells, we performed Gram staining and observed a regular spiral shape of the bacteria (see Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EBV’s ability to infect neuronal cells was established by Jha et al, who were able to successfully infect the neuroblastoma cell line Sh-Sy5y, neurons from the teratocarcinoma line Ntera2, and primary human fetal neurons [ 54 ]. In addition, EBV has been shown to infect HMC-3, a microglial cell line, and U-87 MG, an astrocyte cell line [ 55 ].…”
Section: Introductionmentioning
confidence: 99%
“…EBV's ability to infect neuronal cells was established by Jha et al, who were able to successfully infect the neuroblastoma cell line Sh-Sy5y, neurons from the teratocarcinoma line Ntera2, and primary human fetal neurons [54]. In addition, EBV has been shown to infect HMC-3, a microglial cell line, and U-87 MG, an astrocyte cell line [55]. This review will begin with an overview of EBV reactivation and the lytic and latent cycles, including recent advances in our understanding of how EBV establishes and maintains latency.…”
Section: Introductionmentioning
confidence: 99%